Pengaruh Faktor Fundamental terhadap Return Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - M. Fauzi; Novi Mubyarto; Addiarrahman Addiarrahman (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The purpose of study was find out and analyze the effect of the debt to equity ratio, return on assets and price to book value on stock return in banking companies which is listed on the Indonesian Stock Exchange 2019-2022. In this study using quantitative methods and data analysis method used is panel data analysis. The samples used in this study were 28 banking companies with a total periode of 4 years resulting in 112 data. The results showed that partially, the debt to equity ratio and return on assets has no significant effect on the stock return, while price to book value have a significant effect on the stock return. Simultaneously it shows that the debt to equity ratio, return on assets and price to book value have a significant influence on the stock return in banking companies which is listed on the Indonesian Stock Exchange 2019-2022. The results of the calculation of the coefficient of determination show that the debt to equity ratio, return on assets and price to book value have an influence on the stock return of 22.13% and the remaining 77.87% is influenced by other variables outside of this study.